2021
DOI: 10.2166/wst.2021.638
|View full text |Cite
|
Sign up to set email alerts
|

GC/MS screening of buckthorn phytochemicals and their use to synthesize ZnO nanoparticles for photocatalytic degradation of malachite green dye in water

Abstract: Zinc oxide nanoparticles (ZnO NPs) were biosynthesized. According to GC/MS analysis, chalcone; the main phytochemical; is probably complexed with Zn ions that are then oxidized to ZnO NPs by atmospheric O2 during heating. The ZnO NPs were characterized by TG, FTIR, XRD, FESEM, TEM, eEDAX, and BET surface area analysis. Sphere-like ZnO NPs were formed with 11 nm mean crystallite size, 5.2 m2 g−1 surface area, and 0.02 cm3 g−1 total pore volume. The synthesized ZnO showed excellent photocatalytic degradation (96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Scheme 1 depicts the schematic representation of the synthesis that was performed using our prior methodology with certain adjustments (Hasan et al (2021); (Hasan et al, 2022). Sixty mL of banana peel extract (BPE) and 5 grams of Cu (CH3CO2) 2.H2O (1:12 m/v) were mixed while stirring and heating for 5 minutes.…”
Section: Copper Oxide Nanoparticles (Cuo Nps) Green Synthesis and Cha...mentioning
confidence: 99%
“…Scheme 1 depicts the schematic representation of the synthesis that was performed using our prior methodology with certain adjustments (Hasan et al (2021); (Hasan et al, 2022). Sixty mL of banana peel extract (BPE) and 5 grams of Cu (CH3CO2) 2.H2O (1:12 m/v) were mixed while stirring and heating for 5 minutes.…”
Section: Copper Oxide Nanoparticles (Cuo Nps) Green Synthesis and Cha...mentioning
confidence: 99%
“…Synthesis was carried out according to our previous method with some modifications (Hasan et al, 2021;Hasan et al, 2022) and is shown schematically in scheme 1. Five grams of Cu (CH3CO2) 2.H2O were added to 60 mL BPE (1:12 m/v) under stirring and heating for 5 min.…”
Section: Synthesis and Characterization Of Copper Oxide Nanoparticles...mentioning
confidence: 99%
“…The complex is capped by other organic molecules, terminating further growth of the particles. Calcination of the complex then results in the formation of ZrO2NPs via oxidation by oxygen in air [27,28]. Scheme 1.…”
Section: Mechanism Of Zro2nps Green Synthesismentioning
confidence: 99%
“…To this solution, the PAE (about 200 mL) was added dropwise while the mixture was subjected to continuous stirring. A pale brown precipitate was formed and was magnetically stirred for 2 h, filtered off, washed with DW several times, dried in air for 24 h, and then dried in an oven at 100 • C for 5 h to form a black solid [27], as shown in Scheme 2. The latter solid was carefully milled and calcined, in air, for 3 h at 570 and 700 • C to form ZrO 2 NPs570 and ZrO 2 NPs700, respectively.…”
Section: Synthesis Of Zro 2 Npsmentioning
confidence: 99%
See 1 more Smart Citation